Early Leukocyte Responses in Ex-Vivo Models of Healing and Non-Healing Human Leishmania (Viannia) panamensis Infections - Gomez, Maria Adelaida; Belew, Ashton Trey; Navas, Adriana; Rosales-Chilama, Mariana; Murillo, Julieth; Dillon, Laura A. L.; Alexander, Theresa A.; Martinez-Valencia, Alvaro; El-Sayed, Najib M. (Frontiers in Cellular and Infection Microbiology, 2021)
Early host-pathogen interactions drive the host response and shape the outcome of natural infections caused by intracellular microorganisms. These interactions involve a number of immune and non-immune cells and tissues, along with an assortment of host and pathogen-derived molecules. Our current knowledge has been predominantly derived from research on the relationships between the pathogens and the invaded host cell(s), limiting our understanding of how microbes elicit and modulate immunological responses at the organismal level. In this study, we explored the early host determinants of healing and non-healing responses in human cutaneous leishmaniasis (CL) caused by Leishmania (Viannia) panamensis. We performed a comparative transcriptomic profiling of peripheral blood mononuclear cells from healthy donors (PBMCs, n=3) exposed to promastigotes isolated from patients with chronic (CHR, n=3) or self-healing (SH, n=3) CL, and compared these to human macrophage responses. Transcriptomes of L. V. panamensis-infected PBMCs showed enrichment of functional gene categories derived from innate as well as adaptive immune cells signatures, demonstrating that Leishmania modulates adaptive immune cell functions as early as after 24h post interaction with PBMCs from previously unexposed healthy individuals. Among differentially expressed PBMC genes, four broad categories were commonly modulated by SH and CHR strains: cell cycle/proliferation/differentiation, metabolism of macromolecules, immune signaling and vesicle trafficking/transport; the first two were predominantly downregulated, and the latter upregulated in SH and CHR as compared to uninfected samples. Type I IFN signaling genes were uniquely up-regulated in PBMCs infected with CHR strains, while genes involved in the immunological synapse were uniquely downregulated in SH infections. Similarly, pro-inflammatory response genes were upregulated in isolated macrophages infected with CHR strains. Our data demonstrate that early responses during Leishmania infection extend beyond innate cell and/or phagocytic host cell functions, opening new frontiers in our understanding of the triggers and drivers of human CL.